PROGRAM PELATIHAN GURU BAHASA INDONESIA DALAM MENINGKATKAN KETERAMPILAN MEMBACA PUISI DENGAN MODEL AMATI, TIRU, DAN MODIFIKASI MENGGUNAKAN MEDIA VIDEO PEMBACAAN PUISI PADA SISWA KELAS X DAN XI SMA NEGERI 2 TELUK KERAMAT - Dewi Ferawati; Elsa Mulya Karlina; Effiyadi Effiyadi (Jurnal Pengabdian Kepada Masyarakat, 2022)
Community Service Activities in the form of "Indonesian Language Teacher Training Program in Improving Poetry Reading Skills with Observe, Imitate, and Modify Models Using Poetry Reading Video Media for Class X and XI Students of SMA Negeri 2 Teluk Keramat" went well and according to plan. The participants who attended were very enthusiastic about participating and were very communicative when discussing with the presenters, even though SMA Negeri 2 Teluk Keramat only had two Indonesian language teachers.